Comparison on Critical Thinking Skill and Cognitive Learning Outcome among Students of X Grade with High and Low Academic Ability in Ternate through Reading Questioning Answering (RQA) Strategy - Murni Thalib; A. Duran Corebima; Abdul Ghofur (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: Equity of education can be attained by the implementation of Reading Questioning Answering (RQA) learning strategy. RQA has potential to optimize the critical thinking skills and cognitive learning outcome of students. The aim of this study is to compare the critical thinking skills and cognitive learning outcome among students with different academic ability through RQA strategy. The subjects are students in X grade of SMA Al-Khairat and SMAN 5 Ternate. The result showed that the critical thinking skills percentage of low academic ability students is higher 5.691% than high academic ability students, and the cognitive learning outcome percentage of low academic students is higher 7.067% than high academic students. Therefore, RQA able to empower the critical thinking skills and cognitive learning outcomes of low academic ability studentsKey Words: Critical Thinking Skills, Cognitive learning Outcome, Academic Ability, RQA strategy Abstrak: Upaya pemerataan pendidikan dapat dilakukan melalui penerapan strategi pembelajaran Reading Questioning Answering (RQA). RQA diketahui berpotensi untuk mengoptimalkan keterampilan berpikir kritis dan hasil belajar kognitif siswa. Penelitian ini bertujuan untuk melihat perbandingan keterampilan berpikir kritis dan hasil belajar kognitif antara siswa berkemampuan akademik berbeda melalui strategi RQA. Subjek penelitian adalah siswa kelas X SMA AL-Khairaat dan SMA N 5 Kota Ternate.Hasil penelitian menunjukkan bahwa rata-rata presentase peningkatan keterampilan berpikir kritis siswa berkemampuan akademik rendah lebih tinggi 5,691% dibandingkan siswa berkemampuan akademik tinggi sedangkan rata-rata presentase peningkatan hasil belajar kognitif siswa berkemampuan akademik rendah lebih tinggi 7,067% dibandingkan siswa berkemampuan akademik tinggi. Jadi, RQA mampu memberdayakan keterampilan berpikir kritis dan hasil belajar kognitif siswa pada kemampuan akademik rendahKata kunci: keterampilan berpikir kritis, hasil belajar kognitif, kemampuan akademik, strategi Pembelajaran RQA